Respuesta :

Answer:

a = 3b/b-3

because combined the expression and leaving alone the variable

Answer:

  (A, B) = (4, 12) or (12, 4)

Step-by-step explanation:

An Egyptian fraction is the sum of distinct unit fractions. Here, we're asked to decompose 1/3 into an Egyptian fraction sum of two fractions. There are formulas available when the sum has a numerator value of 2.

Here, the sum is a unit fraction. A reasonable approach is to use 1/(n+1) as the larger portion of 1/n. Then the other portion is 1/(n(n+1)). That is effectively what we end up with here.

__

Multiplying by 3AB gives ...

  AB = 3B +3A

Solving for B, we find ...

  AB -3B = 3A

  B(A -3) = 3A

  B = 3A/(A -3)

In order for A-3 to be a factor of A, or equal to 3, we must have ...

  A-3 = 1  ⇒  A = 4

  A-3 = 3  ⇒  A = 6

  A-3 = 3×3  ⇒  A = 4×3

This will give integer values for B when A is one of 4, 6, or 12. In the case of A=6, the two fractions are equal, which is not what you want

The two solutions are ...

  (A, B) = (4, 12) or (12, 4)